The adoption of information and communication technologies in the design sector and their impact on firm performance: Evidence from the Dutch design sector - Sadaf Bashir; U. Matzat; B. M. Sadowski (International Telecommunications Society (ITS), 2014)
This paper analyzes processes and effects of ICT enabled innovation in the Dutch design sector. Although the adoption of Information and Communication Technologies (ICT) is considered as vital in the design sector, little is known about whether and how ICTs affect the firm performance of small and medium-sized companies (SMEs) in the industry. In introducing a conceptual distinction between ICT supporting the information processing and communication, the paper first examines the determinants of ICT adoption. Next, we analyze the effects of ICT adoption on product and process innovation as well as on firm performance, focusing on the mediating role of the innovation processes. The analyses rest on survey data of a sample of 189 Dutch companies in the Web, Graphic, and Industrial Design Sector in the Netherlands. The results indicate that information processing role of ICT supports the exploitation and communication role facilitates the exploration in organizational learning. The exploitation enables process innovation while exploration enables product innovation. Lastly, Information processing technologies and product innovation are important determinants of superior firm performance.
Keywords: 330